A Two Centre Observational Study of Simultaneous Pulse Oximetry and Arterial Oxygen Saturation Recordings in Intensive Care Unit Patients. Issue 3 (May 2018) - Ebmeier, S. J.; Barker, M.; Bacon, M.; Beasley, R. C.; Bellomo, R.; Chong, C. Knee; Eastwood, G. M.; Gilchrist, J.; Kagaya, H.; Pilcher, J.; Reddy, S. K.; Ridgeon, E.; et al.
The influence of variables that might affect the accuracy of pulse oximetry (SpO2 ) recordings in critically ill patients is not well established. We sought to describe the relationship between paired SpO2 /SaO2 (oxygen saturation via arterial blood gas analysis) in adult intensive care unit (ICU) patients and to describe the diagnostic performance of SpO2 in detecting low SaO2 and PaO2 . A paired SpO2 /SaO2 measurement was obtained from 404 adults in ICU. Measurements were used to calculate bias, precision, and limits of agreement. Associations between bias and variables including vasopressor and inotrope use, capillary refill time, hand temperature, pulse pressure, body temperature, oximeter model, and skin colour were estimated. There was no overall statistically significant bias in paired SpO2 /SaO2 measurements; observed limits of agreement were +/-4.4%. However, body temperature, oximeter model, and skin colour, were statistically significantly associated with the degree of bias. SpO2 <89% had a sensitivity of 3/7 (42.9%; 95% confidence intervals, CI, 9.9% to 81.6%) and a specificity of 344/384 (89.6%; 95% CI 86.1% to 92.5%) for detecting SaO2 <89%. The absence of statistically significant bias in paired SpO2 /SaO2 in adult ICU patients provides support for the use of pulse oximetry to titrate oxygen therapy. However, SpO2 recordings alone should be used cautiously when SaO2 recordings of 4.4% higher or lower than the observed SpO2 would be of concern. A range of variables relevant to the critically ill had little or no effect on bias.